An empirical analysis to derive the essential elasticities for energy demand:a case in Sabah And Sarawak - Yii, Kwang Jing (2016)
"Up to date the Malaysian government has been providing subsidy for various products like energy sources, health, food, education and so on. Among the subsidy given by the government, the most significant amount goes to energy subsidy. Misallocation of resources may lead to over consumption and high national deficit which eventually may lead the country to bankruptcy. However, subsidy cannot be eliminated as long as there is government and the existence of democracy political system. Therefore, the issue that needs to be addressed is to create a mechanism to distribute energy subsidy to the deserving subsidy beneficiaries and not in a blanket basis. This study looks into the impact of subsidy on energy demand in Sabah and Sarawak. Sabah and Sarawak are chosen as the scope of the study due to its difference with Peninsular Malaysia in terms of geographical location, economic activities, affordability, demographic structure and infrastructure. When assessing issues on who are the subsidy beneficiaries, the analysis should be carried out by analyzing the demand for each type of energy based on income groups and location. The demand function was established based on the linear Approximate Almost Ideal Demand System (LA-AIDS) model. With this, the essential elasticities of demand such as own price elasticity, cross price elasticity and expenditure elasticity was derived. The study found that the energy consumption pattern in Sabah and Sarawak referred to multiple fuel model where all income groups preferred to use combination of energy. Besides, the findings of descriptive analysis showed that largely over consumption of electricity was found among low income group In Sabah meanwhile the over consumption of diesel was highly caused by high irteOme group in Sarawak. The own price elasticity indicated that petrol was price elastic among low income and middle Income groups in Sabah meanwhile middle income and high income groups in Sarawak. Besides, diesel was found to be price elastic among high income group in Sabah and Sarawa k. For electricity, high income group in Sabah was found to be responsive to the changes to its own price on the over consumption of electricity meanwhile the responsiveness was found among low income and middle groups in Sarawak. In addition, LPG was price elastic for low income group in Sabah and Sarawak. The findings of cross price elasticities ascertained that electricity was a substitution for LPG and diesel. On the other hand, diesel was a complementary for petrol. Furthermore, the integrated expenditure elasticities indicated that petrol was luxury good for low income group meanwhile high income and middle income groups treated petrol as necessity good. Diesel was apparently a lUXUry good for high income and middle groups meanwhile it was a necessity for low irteOme group. Moreover, electricity and LPG was mostly a necessity good for households in Sabah. In Sarawak, only rural low income and middle income groups treated electricity as necessity meanwhile LPG was a necessity good only for middle income group in urban area. This will help the policy makers to effectively distribute energy subsidy without wastage.